THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE E-FILING SYSTEM IN TAX SERVICES AT TAX ADVISORY PARTNER - Nurazizah; Syarifuddin; Arifuddin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to evaluate the effectiveness of the implementation of the e-Filing system in tax services at the Makassar City Tax Advisory Partner. The e-Filing system is a digital innovation from the Directorate General of Taxes designed to improve the efficiency, effectiveness, and compliance of taxpayers in the Notification Letter (SPT) reporting process. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of e-Filing is able to improve time efficiency, ease of access, and transparency, as well as reduce administrative burden for both tax consultants and taxpayers. However, there are still challenges such as technical constraints, lack of digital literacy, and a system interface that is not yet fully user-friendly. Overall, the e-Filing system makes a positive contribution in supporting more effective and modern tax services. To optimize the use of this system, it is necessary to improve infrastructure, continuous education, and collaboration between the DGT and tax consulting institutions.